RELATIONSHIP BETWEEN INCOME LEVEL, PERCEPTION OF HEALTH SERVICES AND CADRES’S ACTIVITY WITH COMPLIANCE WITH PAYMENT OF INDEPENDENT NATIONAL HEALTH ASSURANCE IN KOLAKA DISTRICT: INDEPENDENT NATIONAL HEALTH ASSURANCE - Jumiati Bandu; La Ode Kamalia; Erwin Azizi Jayadipraja (STIKes Mandala Waluya Kendari, 2021)
Background:Every year, the social insurance administration organisation (BPJS Kesehatan) always experiences a very large deficit. The high number of deficits experienced by the social insurance administration organisation (BPJS Kesehatan) is due to the low level of compliance of contribution payments by independent participants. The purpose of this study was to determine the relationship between income levels, patient perceptions of health services and activeness of cadres with compliance with payment of dues to participants in the Independent National Health Insurance, Kolaka District. Methods:This type of research is a quantitative study with a cross sectional study approach. The population in this study were all 1075 independent National Health Insurance participants. The sample size was 89 respondents who were taken by proportional random sampling. The data were obtained using a questionnaire and then analyzed descriptively and inferentially using the Chi Square test. Result:The results showed that there was a relationship between income levels, patient perceptions of health services and the activeness of cadres with compliance with the payment of dues for participants in the independent national health insurance in Kolaka District, where the p-value <?= 0.05. Conclusion:Perception of health services is the most related factor in comparison to the level of income and activity of the cadres. It is hoped that the social insurance administration organisation (BPJS Kesehatan) will carry out strategies in an effort to increase the regularity or compliance of the independent national health insurance participants and increase the number of cadres.